Experimental optimization of the hundred-keV electron source from laser-driven wire target. (16th June 2020) - Zeng, Yushan; Zhou, Chuliang; Qi, Rong; Li, Zhongpeng; Sun, Haiyi; Tian, Ye; Liu, Jiansheng; Xu, Zhizhan
Abstract: We present the experimental optimization of electrons in the several hundred keV energy range originated from laser-irradiated wire targets. Accelerated by a femtosecond laser pulse, an electron pulse emitted from the wire target was collimated immediately along the wire to a filter unit for the manipulation of energy and spatial distributions. It is shown in simulation that with a pair of magnets as the filter unit, the optimized electrons could serve as a compact and tunable electron source. The proposed system was demonstrated in a proof-of-principle experiment where we attained 1 fC bunch charge with transverse coherence length approaching 1 nm based on a 0.2 TW laser platform. This indicates the scheme as a promising candidate for single-shot electron diffraction.